MODEL PENGENDALIAN PENCEMARAN LAUT UNTUK MENINGKATKAN DAYA DUKUNG LINGKUNGAN TELUK JAKARTA - Irman Firmansyah; Etty Riani; Rahmat Kurnia (Graduate School Bogor Agricultural University (SPs IPB), 2012)
Jakarta Bay is important in coastal management for ecological and economical approach. Another case, it’s also as a river estuary area. Many rivers pass Jakarta Capital City, Bogor, Tangerang and Bekasi areas. The objective of this research were conducted to identify kind of source contamination, assimilation capacities of Jakarta Bay, important elements for contamination effect, and then to construct Sea Contamination Control model, for management policy instruction to prevent Jakarta Bay contamination. This research was operated from Agustus 2005 until April 2006. The analysis of this research used the system approach (dynamic system model). The contamination sources of this area were domestic waste, industrial disposal and waste of market. This contamination levels have an exceeded assimilation capacities: TDS is equal to 2 313 609.07 ton/month, PO4 is equal to 518.85 ton/month, SO4 is equal to 141 610.11 ton/month, MBAS is equal to 441.87 ton/month, KMnO4 is equal to 23 785.43 ton/month, BOD is equal to 16 369.05 ton/month, dan COD is equal to 52 983.15 ton/month. The interpretative structural modelling (ISM) indicated that there are five primary factors, namely law enforcement, good cooperation of stakeholders, good relation of area management, good compromise of need assessment, vision, target and mission to managing the environment. Keywords: assimilation capacities, contamination, dynamic system model, jakarta bay